The Effectiveness of Anagram Technique in Teaching Vocabulary - Rosadi, Ahdian (Universitas Hamzanwadi, 2017)
This study aimed at finding out the effectiveness of anagram technique in teaching vocabulary at the seventh grade of MTs. Al-Majidiyah NW Majidi in the school year 2015-2016. This study is a pre-experimental design. The sample was one class consisted of 30 students. The data collection was done by administering pre-test and post-test in the form of objective test. In the data analysis, Paired Sample T-Test was used to prove the hypothesis. Based on the data gained, it was found that the mean score of the pre-test was 18.67 while the mean score of the post-test was 25.30. It meant that there was a significant difference in the mean scores between pre-test and post-test, t(df=29) = 19.282 at p = 0.000 that was lower than 0.05. It means that the alternative hypothesis was accepted which indicates that anagram technique was significantly effective in teaching vocabulary. Additionally, the result of this research shows that anagram is a good vocabulary learning strategy. It encourages greater self-direction for learners. Thus, it is strongly suggested that teachers apply this technique to help improve students’ vocabulary.